The Implementation of Writing Assessment in Learning in SMA Negeri 5 Enrekang - Muftihaturrahmah Burhamzah; Alamsyah Alam (LETS: Journal of Linguistics and English Teaching Studies, 2022)
The purpose of this study is to (1) explain the implementation of writing assessment procedures by English teachers at SMA Negeri 5 Enrekang in helping students learn to write and (2) discuss the challenges experienced by English teachers at SMA Negeri 5 Enrekang in conducting the assessments. A qualitative descriptive design was adopted in this investigation. The English teacher at SMA Negeri 5 Enrekang is the focus of this study, and the goal is to obtain an honest assessment of the English instructor. The observation method, interview method, and documentation method were utilized to collect data. Observation and documentation were used to gather data on the implementation of the authentic assessment by the English teacher at SMA Negeri 5 Enrekang, as well as observation and interviews to get data on the impediments to the implementation of the authentic assessment. The findings of this study show that the English teacher's evaluation in writing learning at SMA Negeri 5 Enrekang employs a test-and-non-test (portfolio and performance) strategy. This indicates that the evaluation was done correctly. Despite the fact that the evaluation was carried out honestly, it is not ideal due to obstacles in its execution. English teacher has number of challenges while conducting authentic assessments, including: (1) time management issues, (2) non-conducive classroom circumstances, (3) inadequate facilities and equipment, and (4) a lack of understanding of the assessment system in place. Because accurate evaluation is so difficult, it requires a delicate balance of judgment between knowledge and experience.